Effect of the CONACYT scholarship in terminal efficiency - Miguel Álvarez Gómez; Edith Gómez Polanco; María Morfín Otero (Universidad Autónoma de Baja California, 2012)
This article research on the impact of the scholarship for postgraduate studies awarded by CONACYT in terminal efficiency postgraduate in Mexico. Analyzed in the master in technologies for learning in the Center University of the coast of the University of Guadalajara (UdeG). The results show that the studied variables are independent. The study highlighting the fact that there is therefore no effect or relationship on postgraduate scholarship CONACYT, as they are granted at the present time, with students certification and therefore with the terminal efficiency. Suggests some changes in the provision of economic aid to become a more determinant factor.